Investigating the effects of watson-based education on depressive symptoms, hope, and pain in cancer patients undergoing chemotherapy: a randomized controlled clinical trial - Fateme Rajabi; Mostafa Bijani; Mohammad Mehdi Naghizade; Leila Nikrouz (BMC Psychology)
Abstract Background Cancer is among the most important chronic illnesses and one of the main public health concerns worldwide, which has significant physical, social, psychological, and spiritual consequences for the patient and his family. This disease reduces hope in patients and leads to depressive symptoms as well as pain. This research was designed and performed to explore the impact of teaching according to Watson’s theory on depressive symptoms, hope, and pain in patients suffering from cancer undergoing chemotherapy in southern Iran. Methods This is a randomized controlled trial research without blinding. A total of 120 randomly selected patients were assigned to two intervention groups (n = 60) and a control group (n = 60). The intervention underwent education according to Watson’s theory. Data were collected using the Beck Depression Inventory (BDI), Miller Hope Scale (MHS), and McGill Pain Questionnaire (MPQ). Data analysis was performed using SPSS version 22. To analyze the data, we used descriptive statistics. Accordingly, inferential statistics applied included chi-square, independent-samples t-test, and repeated measures (ANOVA). We also used analysis of covariance (ANCOVA) to determine whether there are any significant differences between the two groups. Significance level was considered as p < 0.05. Results Mean scores for depressive symptoms, hope, and pain intensity, measured two weeks and two months after the intervention, were significantly higher in the intervention group (p < 0.05). However, for the control group, the difference was not statistically significant. Conclusion Education based on Watson’s theory positively improved hope and reduced depressive symptoms as well as pain intensity in cancer patients. Nursing managers and health system policy makers can use this educational approach for people with other chronic conditions. Iranian registry of clinical trials IRCT registration number: IRCT20190917044802N6. Registration date 31/7/2022.